Compiler construction 20th international conference, CC 2011, held as part of the joint European conferences on theory and practice of software, ETAPS 2011, Saarbrücken, Germany, March 26-April 3, 2011. proceedings - Knoop, Jens (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 20th International Conference on Compiler Construction, CC 2011, held in Saarbrucken, Germany, March 26 - April 3, 2011, as part of ETAPS 2011, the European Joint Conferences on Theory and Practice of Software. The 15 revised full papers presented together with the abstract of one invited talk were carefully reviewed and selected from 52 submissions. The papers are organized in topical sections on JIT compilation and code generation, program analysis, reversible computing and interpreters, parallelism and high-performance computing, and task and data distribution.